Experimental and Numerical Study of Soil Strata for Underground Transportation System: A Case Study - Osamah Alqawas; Md. Rehan Sadique; Zaid Mohammad; Sanan Husain Khan (Civil Engineering Journal, 2024)
In the current capital of Yemen, Sana’a, a time-efficient and economical transportation system is one of the greatest challenges to overcome the increasing urbanization for many years. Rapid transport systems use tunnel structures to reach the city's most inaccessible areas. Given the Gulf's geopolitical unrest, these structures could also serve as emergency shelters. Consequently, this research conducted an experimental soil exploration investigation in Sana'a, Yemen, to identify potential tunneling sites for the city's rapid transit system. The field exploration, in-situ, and laboratory soil testing at the four locations were performed with the collaboration of the Ministry of Public Works & Highways, Yemen. Further, to calculate the geotechnical parameters for tunnel design, numerical analysis has been carried out using the finite element package ABAQUS, and two-dimensional plane-strain numerical models of underground tunnel structure have been developed to conduct the parametric study in different soil types and boundary conditions under static loading. The material behavior of soil strata has been incorporated into the well-known Mohr-Coulomb constitutive model. The field investigation found that the geotechnical properties of the soil strata in Sana’a have a lot of variation. The numerical study shows that the maximum deformation in the concrete liner of the tunnel was observed at the crown of the tunnel. The ovalling effect in tunnel concrete liner was also seen in all the tunnel models, and the maximum ground settlement at sites 1, 2, 3, and 4 was estimated to be approximately 4, 25, 17, and 11 mm, respectively. Doi: 10.28991/CEJ-2024-010-01-03 Full Text: PDF